Children, sexuality and child sexual abuse - Kenny, Dianna T. (Routledge, 2018)
Introduction -- Overview: childhood, sex and society -- Sexual development and behaviour in children -- Adverse experiences in childhood -- Prevalence of child sexual abuse -- Abuse and neglect of children in indigenous communities -- Institutional child sexual abuse -- Disclosure of child sexual abuse -- Assessment of child sexual abuse -- The effects of child sexual abuse -- Memory -- When memory deceives: false and recovered memories -- Young people who sexually offend